Analisis Pengaruh Pendistribusian Zakat Produktif Secara Adil Terhadap Pengentasan Kemiskinan Mustahik Di Kabupaten Tanah Datar - Alfiona, Fifa; Taufiq, Muhammad (PT. ALHAFI BERKAH INDONESIA, 2023)
This study aims to determine the effect of the distribution of productive zakat on poverty alleviation mustahik in Baznaz, Tanah Datar District. Using Quantitative Research with a research analysis tool, namely Simple Linear Regression (RLS). Where the population and sample in this study used the saturated sample method of 57 mustahik. The research data uses a questionnaire with a Likert Scale and uses a Hypothesis Test (partial test - t test), test the coefficient of determination (R-Square). The results of this study explain that the distribution of productive zakat partially has a significant effect indicated by the sig value < alpha value (0.00 < 0.05). Then the distribution of productive zakat has a big influence in alleviating the poverty of mustahik, namely by 79.3 percent, this is because the Baznaz institution of Tanah Datar Regency has distributed productive zakat fairly based on old economic principles. while the remaining 20.7 percent poverty alleviation mustahik is influenced by other variables not examined in this article such as the variable of public awareness in paying zakat, collaboration with stakeholders and fundraising by amil zakat institutions.